Studi Kasus Penerapan Senam Ergonomis Pada Penderita Hipertensi Di Puskesmas Mamburungan Kota Tarakan - Renna Youfristiya Sari; Donny Tri Wahyudi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Ergonomic exercises can lower blood pressure by restoring the elasticity of blood vessels and improving blood flow. The research method used was a case study involving 2 different respondents. The aim of this research is to analyze the effectiveness of applying ergonomic exercises to reduce blood pressure in hypertensive clients. This type of research is descriptive in the form of a case study. The subjects in this study were two individuals with the same case in two different families with hypertension. Those who were given the same treatment where blood pressure was measured pre and post doing ergonomic exercises. The implementation was carried out 3 times a week for a duration of 30 minutes. The results of the study showed that the blood pressure of the respondents experienced a decrease in blood pressure in systole 14-37 MmHg and diastole 4-15 MmHg. The application of ergonomic exercises is effective in reducing blood pressure in hypertension sufferers.